2003
DOI: 10.1042/cs20030080
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory-related arterial pressure variability as an indicator of graded blood loss: involvement of the autonomic nervous system

Abstract: During positive pressure mechanical ventilation, percentile systolic pressure variation (%SPV) or respiratory-related arterial pressure variability (RAPV) have both been used in assessment of graded haemorrhage. We aimed to investigate whether changes in %SPV and RAPV are correlated during graded haemorrhage (by 5, 10 or 20% of the estimated blood volume) in anaesthetized positive pressure ventilated rats and to investigate the involvement of autonomic regulation. Saline vehicle or atropine produced no discern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 23 publications
1
26
0
1
Order By: Relevance
“…7,8 Instead, dynamic haemodynamic measurements during positive pressure ventilation, systolic pressure variation (SPV), stroke volume variation (SVV), and PPV, have been reported to better predict fluid responsiveness. 10,14,[27][28][29] In addition, changes in aortic blood flow velocity and VTI Ao by pulse-Doppler echocardiography and collapse of the superior vena cava or the inferior vena cava have been found to be predictors of fluid responsiveness during mechanical ventilation. 23,24,[30][31][32] These dynamic methods are quite accurate in controlled situations but may have several limitations in clinical practice.…”
Section: Discussionmentioning
confidence: 97%
“…7,8 Instead, dynamic haemodynamic measurements during positive pressure ventilation, systolic pressure variation (SPV), stroke volume variation (SVV), and PPV, have been reported to better predict fluid responsiveness. 10,14,[27][28][29] In addition, changes in aortic blood flow velocity and VTI Ao by pulse-Doppler echocardiography and collapse of the superior vena cava or the inferior vena cava have been found to be predictors of fluid responsiveness during mechanical ventilation. 23,24,[30][31][32] These dynamic methods are quite accurate in controlled situations but may have several limitations in clinical practice.…”
Section: Discussionmentioning
confidence: 97%
“…Experiments under various physical conditions including external stimuli are thus necessary to make MF more applicable. The mechanism underlying HF has not been adequately explained despite several studies indicating that it is a mechanical consequence of respiration [12, 13] and other studies suggesting an association between HF and ANS, particularly the β-adrenergic system [1416]. To make progress in the availability of SBPV frequency analysis for the evaluation of sympathetic cardiovascular function, the association between the sympathetic nervous system and SBPV must be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies of the involvement of sympathetic cardiovascular function in SBPV (particularly in respiratory HF) are conducted under anesthesia [1416]; therefore, little is known concerning the natural responses to stimuli under unanesthesia when ANS is not suppressed. It is meaningful to examine the ANS response in a conscious state in order to evaluate complicated pathological conditions (e.g., chronic pain) in human [17] and animal models [18–20].…”
Section: Introductionmentioning
confidence: 99%
“…Later studies (22,23) demonstrated that the BHFn provides a valid assessment of cardiac sympathetic regulations in anesthetized and ventilated rats. A recent study by Lai and coworkers (27) also showed that the BHFn is an indicator of graded hemorrhage and is dependent on autonomic function, especially cardiac sympathetic functions. The present study further elucidates that the BHFn increases significantly within 6 secs after reventilation and that the increase is attenuated by ␣-adrenergic, ␤-adrenergic, and muscarinic blockades.…”
Section: Discussionmentioning
confidence: 92%
“…Power of the low-frequency component (BLF), normalization high-frequency component (BHFn) of the SAP spectrogram, and highfrequency component (HHF) of the interbeat spectrogram were quantified (19,21,22). BHFn, BLF, and HF provided markers of cardiac sympathetic modulation (18,22,23,27), sympathetic vasomotor activity (19, 29 -33), and cardiac vagal activity (30,31,34,35), respectively.…”
Section: Methodsmentioning
confidence: 99%